THE KURDISH PROBLEM IN DEMOCRATIC PARTY PERIOD: ITS PROGRESS AND İNFLUENCES - Fuat UÇAR (Fırat University, 2019)
Kurdish problem has been an issue that keeps sensibility in the presence of executives from the periods of Abdulhamid II, Union and Progress Association in Ottoman Empire to the Republic period. After the proclamation of the Republic, the Kurdish problem that has kept up-to-date in single and multi party periods was subjected to different practices out of traditional politics in the period of Democratic Party in 1950-1960. In this period, the Kurdish problem, apart from which was perceived as only public peace problem by executives, got into a “detente term” as a result of democratisation that developed with internal and external factors. During this period, that the ones sent to exile in single party term got into parliament as delegate by being allowed to turn back and appropriate became the most important developments. The Kurdish problem within this scope became awareness regarding Kurdish identity with coming out of removing some associations and publications thanks to the removal of Settlement Law in 1934 and Public Inspectorship. Once more in the period of Democratic Party, that the executives cooperated with Kurdish aga and sheiks as a result of various liberal politics applied all around the country caused Democratic Party to gain more strength in comparison to Republican People’s Party in eastern and southeastern regions. The political and ideological awareness regarding Kurdish identity with the effect of this alliance in consequence of political and economical developments in Democratic Party period became one of the most important factors of Kurdish movement in later periods.